2021
DOI: 10.1042/bst20200861
|View full text |Cite
|
Sign up to set email alerts
|

Links between the unfolded protein response and the DNA damage response in hypoxia: a systematic review

Abstract: Hypoxia is a feature of most solid tumours and predicts for poor prognosis. In radiobiological hypoxia (<0.1% O2) cells become up to three times more resistant to radiation. The biological response to radiobiological hypoxia is one of few physiologically relevant stresses that activates both the unfolded protein and DNA damage responses (UPR and DDR). Links between these pathways have been identified in studies carried out in normoxia. Based in part on these previous studies and recent work from our lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 108 publications
0
35
1
Order By: Relevance
“…The apoptotic effect was confirmed by annexin V staining that increased in BC3 cells, particularly following Zinc/radiation treatment ( Figure 3 C). ER stress/UPR activation have been shown to influence DNA repair following treatment with genotoxic agents [ 27 ]; therefore, next we investigated whether Zinc-enhanced cell death could correlate with increased DNA damage in cells exposed to low-dose radiation. At this aim we assessed the appearance of the phosphorylated form of H2AX ( γ H2AX) and, as shown in Figure 3 D,G, we found that radiation increased γ H2AX and that it further increased with Zinc/radiation combination.…”
Section: Resultsmentioning
confidence: 99%
“…The apoptotic effect was confirmed by annexin V staining that increased in BC3 cells, particularly following Zinc/radiation treatment ( Figure 3 C). ER stress/UPR activation have been shown to influence DNA repair following treatment with genotoxic agents [ 27 ]; therefore, next we investigated whether Zinc-enhanced cell death could correlate with increased DNA damage in cells exposed to low-dose radiation. At this aim we assessed the appearance of the phosphorylated form of H2AX ( γ H2AX) and, as shown in Figure 3 D,G, we found that radiation increased γ H2AX and that it further increased with Zinc/radiation combination.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly important to assess the impact of each UPR sensor on DDR molecules in order to design the most appropriate combination therapies able to counteract the mechanisms that allow cancer cells to survive, despite the exposure to anti-cancer treatments. Interestingly, some molecules belonging to UPR, besides ER stress, can be activated by DNA damage [ 61 ]. For example, ATF4, a transcription factor involved in the up-regulation of the pro-apoptotic molecule CHOP, can be activated by both UPR and DDR signaling.…”
Section: Stress Response Pathways and Cancer Survivalmentioning
confidence: 99%
“…DNA damaging stimuli such as UV, IR and exposure to chemicals can also damage cellular proteins. Therefore, DNA damage is often associated with ER stress, which elicits the subsequent unfolded protein response (UPR) in stressed cells [33]. Like DDR, UPR can result not only in cellular protection by facilitating the degradation of misfolded proteins, but also in the induction of apoptosis when cellular stresses surpass the cellular repair capacity [34,35].…”
Section: Role Of Atm In Apoptosismentioning
confidence: 99%